2018
DOI: 10.1007/s00213-018-4991-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between hypothermia and neurotoxicity caused by mephedrone and methcathinone in TPH2 knockout mice

Abstract: Serotonin is a key mediator of pharmacological hypothermia induced by mephedrone and methcathinone, but these body temperature effects do not contribute to dopamine nerve ending damage observed in mice following treatment with mephedrone, methcathinone or 4-methyl-methamphetamine. Thus, the key component of methamphetamine neurotoxicity lacking in mephedrone remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The rationale for this experiment was the observation that while both METH and 4-MMC produce hyperthermia, 4-MMC has also been reported to produce a brief hypothermic response. However, they reported that although the knockout mice did not experience the characteristics hypothermic response, no increase in toxicity was observed in the knockouts vs. the wild-types ( Anneken et al, 2019 ). Another possibility is that 4-MMC has a different effect of mitochondria than METH, which has been associated with mitochondrial-dependent mechanisms of toxicity ( Shin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this experiment was the observation that while both METH and 4-MMC produce hyperthermia, 4-MMC has also been reported to produce a brief hypothermic response. However, they reported that although the knockout mice did not experience the characteristics hypothermic response, no increase in toxicity was observed in the knockouts vs. the wild-types ( Anneken et al, 2019 ). Another possibility is that 4-MMC has a different effect of mitochondria than METH, which has been associated with mitochondrial-dependent mechanisms of toxicity ( Shin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question as to what pharmacological differences between 4-MMC and METH result in the latter much more readily inducing neurotoxicity in animal models. Anneken et al (2018) hypothesized that the proposed difference could be due to differences in how METH and 4-MMC access the drug-releasable pool of DA. However, their experiments showed that combining the drugs with L-DOPA, which increases the size of the release pool, did in fact not precipitate any 4-MMC neurotoxicity while enhancing the toxic effects of METH.…”
Section: Discussionmentioning
confidence: 99%